Role of macrophage and associated cytokines in the regulation of breast tumour lymphovascular invasion - Ahmad, N.S. (2016)
Lymphovascular invasion, including both blood and lymphatic vessel invasion, is an important step in tumourigenesis and is a prerequisite event in the complex process of metastasis. In breast cancer, data suggest that lymphatic vessels plays a significant role by being the major route for lymphatic vessel invasion (LVI) and that inflammatory cells, may be involved in its regulation. Macrophage, a major component of inflammatory infiltrate, has been shown to be importance in tumour growth and metastasis. The biomolecular mechanisms by which macrophage can mediate dissemination of tumour cells through the lymphatic compartment are, however, not yet fully understood.